2015
DOI: 10.1159/000371896
|View full text |Cite
|
Sign up to set email alerts
|

Sour Sweets and Acidic Beverage Consumption Are Risk Indicators for Dental Erosion

Abstract: This study aimed to investigate the association between dental erosive wear and potential background, behavioural and dietary risk indicators and to assess whether there is a dose-response relationship between the level of acidic beverage consumption and dental erosive wear among adolescents. Of 846 adolescents (aged 16-18 years) scheduled for dental recall examinations, 795 (94%) accepted to participate. All participants completed a self-administered questionnaire regarding their background (gender and age), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 30 publications
5
63
0
16
Order By: Relevance
“…A very recent study showed that not only the pH of the drinks but also the high intake of sour sweets could increase the risk of dental erosive wear [34].…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study showed that not only the pH of the drinks but also the high intake of sour sweets could increase the risk of dental erosive wear [34].…”
Section: Discussionmentioning
confidence: 99%
“…This randomized controlled crossover clinical trial was designed to move a step forward towards the understanding of the salivary pH kinetics after the consumption of sour candies, whose erosive potential have been demonstrated in an observational survey [18,19] and in laboratory experimental investigations [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the findings of an in vitro study have suggested that saliva may offer reduced protection to enamel against the erosive effects of sour candies [17]. Third, sour candies have been significantly associated with dental erosion in children [18] and adolescents [19] in a frequency-dependent manner. In the former quoted survey, children who consumed sour candies more than twice daily, once daily and 2-4 times per week presented, respectively, nearly 24, 18 and 8 times higher risk of having dental erosion compared with those who did not eat sour candies at all.…”
Section: Introductionmentioning
confidence: 99%
“…Sovik et al also prove that dental erosive wear, symptomatically measured mainly by DH, is due to high consumption of sour sweets and sports drinks (10).…”
Section: Table 1: Hypersensitivity Manifestations In Relation To Diffmentioning
confidence: 99%